AINUN’S MARITAL COMMITMENT IN HABIBIE’S NOVEL HABIBIE & AINUN - Lestari Sukmawati Br Parangin-Angin; Sri Wulan; Asnani Asnani (JOURNAL OF LANGUAGE, 2022)
This study deals with the Ainun’s marital commitment in Habibie’s Novel Habibie Ainun. The novel is taken from the true story of the author. In this novel, Ainun teaches readers how to carry out their obligations as a good wife and be able to take care of children and home with patience and faithfulness. The marital commitment contained in this novel is Ainun’s way of becoming a wife. The analysis is based on the theory of Marital Commitment by Adams Jones. They explain there are three commitments. They are personal, mental and structural commitments. In completing the analysis, the study uses descriptive qualitative method. The result of this study is presented in the form of description. In the analysis, it is shown that Ainun proves her personal and mental commitments in the novel. She always prioritizes her family. She is also described as a faithful companion. She always accompanies her husband in every up and down moments. These descriptions are as her personal commitment in her marriage. Then, she is portrayed as a religious woman who always cares about the welfare of the nation. Thus, this leads us that Ainun shows her mental commitment. But, structural commitment cannot be shown in the novel. All in all, the novel may imply a moral lesson about how to build a solid commitment in a marriage.